Implied volatility of structured warrants: Emerging market evidence - Mohamad, Azhar; Samsudin, Najmi Ismail Murad; Sifat, Imtiaz, Mohammad (Elsevier, 2021)
This paper examines the informational content of Implied Volatility (IV) for 493 Malaysian and 945 Thaistructured call warrants from 2014 to 2015. Unlike a regular warrant (issued by the firm) and attached to bonds, loan stocks, or preferred stocks as sweeteners, a structured warrant is issued by a third party.. Structured warrant is a prevalent exchange-traded instrument in South-East Asian countries. This study is among the first to examine the IV of structured warrants using emerging market datasets from BursaMalaysia and the Stock Exchange of Thailand. Our predictive regression models compare IV’s effectiveness in anticipating future realized volatility vis-à-vis historical volatility. We record that IV in both exchanges contains relevant information about future realized volatility only on a handful of occasions. Additionally,structured warrants’ IV is a mostly biased predictor with a diminutive efficiency threshold. Our findingsbear implications for the region’s derivatives market growth and risk management practices.